2015
DOI: 10.1016/j.breast.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Tumor size and stage of breast cancer in Côte d'Ivoire and Republic of Congo – Results from population-based cancer registries

Abstract: These results underscore the importance of increased awareness about early detection of breast cancer, as well as expansion of the capacity to provide appropriate diagnosis, treatment, and palliative care in sub-Saharan Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…An equally high proportion of late‐stage disease (77%) was described in a meta‐analysis including 24,213 women from a variety of hospital settings within SSA . A study on breast cancer stage at diagnosis using population‐based data in Abidjan, Cote d'Ivoire and Brazzaville, Congo for cases diagnosed from 2008 to 2009 reported 74 and 81% of breast cancers diagnosed at Stages III and IV . It has to be noted that there is a considerable delay between first symptoms and presentation to health care practitioner; a recent systematic review found between 3 to over 6 months delay, and there is an additional 3–6 months interval between first presentation to health care practitioner and confirmation of diagnosis of breast cancer in SSA; while in comparison, the median time from first presentation at the health care setting to diagnosis in 2004–2005 was on average 25 days (range:14–44 days) in the Aarhus county of Denmark.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An equally high proportion of late‐stage disease (77%) was described in a meta‐analysis including 24,213 women from a variety of hospital settings within SSA . A study on breast cancer stage at diagnosis using population‐based data in Abidjan, Cote d'Ivoire and Brazzaville, Congo for cases diagnosed from 2008 to 2009 reported 74 and 81% of breast cancers diagnosed at Stages III and IV . It has to be noted that there is a considerable delay between first symptoms and presentation to health care practitioner; a recent systematic review found between 3 to over 6 months delay, and there is an additional 3–6 months interval between first presentation to health care practitioner and confirmation of diagnosis of breast cancer in SSA; while in comparison, the median time from first presentation at the health care setting to diagnosis in 2004–2005 was on average 25 days (range:14–44 days) in the Aarhus county of Denmark.…”
Section: Discussionmentioning
confidence: 99%
“…21 A study on breast cancer stage at diagnosis using population-based data in Abidjan, Cote d'Ivoire and Brazzaville, Congo for cases diagnosed from 2008 to 2009 reported 74 and 81% of breast cancers diagnosed at Stages III and IV. 22 It has to be noted that there is a considerable delay between first symptoms and presentation to health care practitioner; a recent systematic review found between 3 to over 6 months delay, and there is an additional 3-6 months interval between first presentation to health care practitioner and confirmation of diagnosis of breast cancer in SSA 23 ; while in comparison, the median time from first presentation at the health care setting to diagnosis in 2004-2005 was on average 25 days (range:14-44 days) in the Aarhus county of Denmark. The median overall time from first symptom recognition to diagnosis has been estimated at 7.9 months in Accra, Ghana, 24 8.5 months in Western Cape, South Africa, at more than 10 months in Abidjan, Cote d'Ivoire 25 and at 15 months in rural Rwanda 26 ; in contrast, in 2006, about 30% of all breast cancer cases in England, Scotland and Wales were diagnosed asymptomatically by screening.…”
Section: Discussionmentioning
confidence: 99%
“…On average, 50–75% of women present with very advanced disease in Africa [ 36 ]. Islami et al reported 74 and 81% advanced stage at presentation in Cote d’Ivoire and the Democratic Republic of Congo respectively [ 37 ], Soliman et al reported 90% of breast cancer patients present with advanced disease in Niger; invariably mastectomy is the most common surgical procedure performed [ 38 ]. Reports from Eritrea and Tanzania indicate that up to 99% of patients undergo mastectomy for various reasons including advanced stage and lack of other modalities of treatment [ 39 , 40 ].…”
Section: Surgical Managementmentioning
confidence: 99%
“… 3 , 81 Most hospitals in WA lack access to trained professionals, health care coverage, 61 screening technologies, and treatment facilities. 84 In the developing world, it is common for clinical oncologists to perform both radiation and medical oncology. 85 As these oncologists may not be able to gain sufficient expertise in both fields, patients with cancer may not receive optimal care.…”
Section: Environmental and Social Risk Determinants Of Tnbc In Wamentioning
confidence: 99%